Cross country : a novel - Patterson, James, 1947- (New York : Little, Brown, 2008)
When the home of Alex Cross's oldest friend, Ellie Cox, is turned into the worst murder scene Alex has ever seen, the destruction leads him to believe that he's chasing a horrible new breed of killer.
Keywords: Cross, Alex (Fictitious character) -- Fiction; African American psychologists -- Fiction; Washington (D.C.) -- Fiction; Suspense fiction; Mystery fiction